MicroRNAs Clustered within the 14q32 Locus Are Associated with Endothelial Damage and Microparticle Secretion in Bicuspid Aortic Valve Disease - Martínez-Micaelo, Neus; Beltrán-Debón, Raúl; Aragonés, Gerard; Faiges, Marta; Alegret, Josep M. (Frontiers in Physiology, 2017)
Background: We previously described that PECAM+ circulating endothelial microparticles (EMPs) are elevated in bicuspid aortic valve (BAV) disease as a manifestation of endothelial damage. In this study, we hypothesized that this endothelial damage, is functionally related to the secretion of a specific pattern of EMP-associated miRNAs. Methods: We used a bioinformatics approach to correlate the PECAM+ EMP levels with the miRNA expression profile in plasma in healthy individuals and BAV patients (n=36). In addition, using the miRNAs that were significantly associated with PECAM+ EMP levels, we inferred a miRNA co-expression network using a Gaussian graphical modelling approach to identify highly co-expressed miRNAs or miRNA clusters whose expression could functionally regulate endothelial damage. Results: We identified a co-expression network composed of 131 miRNAs whose circulating expression was significantly associated with PECAM+ EMP levels. Using a topological analysis, we found that miR-494 was the most important hub within the co-expression network. Furthermore, through positional gene enrichment analysis, we identified a cluster of 19 highly co-expressed miRNAs, including miR-494, that was located in the 14q32 locus on chromosome 14 (p-value=1.9×10-7). We evaluated the putative biological role of this miRNA cluster by determining the biological significance of the genes targeted by the cluster using functional enrichment analysis. We found that this cluster was involved in the regulation of genes with various functions, specifically the “cellular nitrogen compound metabolic process” (p-value=2.34×10-145), “immune system process” (p-value=2.57×10-6), and “extracellular matrix organization” (p-value=8.14×10-5) gene ontology terms and the “TGF-β signalling pathway” KEGG term (p-value=2.59×10-8). Conclusions: Using an integrative bioinformatics approach, we identified the circulating miRNA expression profile associated with secreted PECAM+ EMPs in BAV disease. Additionally, we identified a highly co-expressed miRNA cluster that could mediate crucial biological processes in BAV disease, including the nitrogen signalling pathway, cellular activation, and the transforming growth factor beta signalling pathway. In conclusion, EMP-associated and co-expressed miRNAs could act as molecular effectors of the intercellular communication carried out by EMPs in response to endothelial damage.